2016
DOI: 10.18632/oncotarget.10406
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63 mediates cellular survival and metastasis in canine osteosarcoma

Abstract: p63 is a structural homolog within the 53 family encoding two isoforms, ΔNp63 and TAp63. The oncogenic activity of ΔNp63 has been demonstrated in multiple cancers, however the underlying mechanisms that contribute to tumorigenesis are poorly characterized. Osteosarcoma (OSA) is the most common primary bone tumor in dogs, exhibiting clinical behavior and molecular biology essentially identical to its human counterpart. The purpose of this study was to evaluate the potential contribution of ΔNp63 to the biology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 50 publications
(67 reference statements)
3
25
1
1
Order By: Relevance
“…Interestingly, in contrast to our findings in this study, ΔNp63α was reported to be positively regulated by PI3K signaling in keratinocytes (63), and by the EGF receptor in squamous cell carcinoma cells (64). Notably, up-regulation of ΔNp63α has been implicated in promoting tumor metastasis in several settings (58)(59)(60). These inconsistencies may reflect differences between oncogenic and normal physiological signaling, depending on the cellular context.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, in contrast to our findings in this study, ΔNp63α was reported to be positively regulated by PI3K signaling in keratinocytes (63), and by the EGF receptor in squamous cell carcinoma cells (64). Notably, up-regulation of ΔNp63α has been implicated in promoting tumor metastasis in several settings (58)(59)(60). These inconsistencies may reflect differences between oncogenic and normal physiological signaling, depending on the cellular context.…”
Section: Discussioncontrasting
confidence: 82%
“…Accumulating evidence indicates that decreased ΔNp63α expression may play a causative role in promoting cell motility and cancer metastasis (42,(58)(59)(60). In this study, we show that activation of three cancer signaling pathways, including PI3K, Ras, and Her2 signaling, promotes cancer cell motility and tumor metastasis by commonly targeting and repressing ΔNp63α expression.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of OS is generally bad for the distal metastases [1-3]. In nowadays, the prognosis of patients with early OS could be improved with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…To be successful in seeding distant sites, these metastatic precursors must acquire the ability to invade through the tissue matrix, intravasate into the circulation, arrest within the target tissue, extravasate, survive within each of these diverse and heterotypic environments, and then proliferate within the target organ in ways that recapitulate the primary solid tumor (111). Doing so requires the acquisition of myriad behaviors not typical of the cells of origin, and these transformed phenotypes can arise from abnormal activation of cell-autonomous pathways that endow tumor cells with, for example, resistance to apoptosis (112) or the ability to affect unusually high levels of capped mRNA translation (22). Beyond these shifts in behavior that represent intrinsic properties of the malignant cells themselves, disseminated tumor cells often acquire additional malignancy-associated behaviors from interactions with the normal tissues that surround them within the metastatic niche (113).…”
Section: Mouse Models Of Osteosarcoma Metastasismentioning
confidence: 99%